Internalisasi Nilai Kemanusiaan Sebagai Strategi Pencegahan Bullying di SMPN 9 Banjarmasin - Darmawati Darmawati; Mariatul Kiptiah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the internalization of humanitarian values as a strategy to prevent bullying at SMPN 9 Banjarmasin. Using a descriptive qualitative approach, data were collected through observation, interviews with nine informants, and documentation. Data were analyzed using the Miles and Huberman model and validated through triangulation. The findings indicate that empathy is developed through social experiences, teacher role-modeling, and habituation. Social care is reflected in empathy, responsibility, solidarity, and student participation. Pancasila Education contributes significantly to the internalization of these values through active learning methods. The study concludes that the internalization of humanitarian values effectively supports the development of an anti-bullying school culture in accordance with the second principle of Pancasila.